Barriers and Predictors of Phsyical Activity Behaviour in Adolescent Upper Secondary Student - Dhini Rafika Syafriani; Jajat; Kuston Sultoni (Universitas Negeri Semarang, 2025)
This study aims to identify perceived barriers and evaluate 24-hour physical activity behavior in middle and high school students. The phenomenon of declining participation in physical activity among adolescents is a concern, considering its impact on physical and mental health. This study used a quantitative approach with a descriptive design, involving 100 students in Subang Regency as the research sample. The instruments used included a physical activity barriers questionnaire and a 24-hour movement behavior questionnaire. The results of the Spearman correlation test showed a significant relationship between barriers and low involvement in physical activity, with a value of r = 0.325 and a significance of p = 0.001. The most common barriers found were lack of sports facilities, academic pressure, and minimal social support. This study confirms that although students are aware of the importance of physical activity, external and internal barriers remain a barrier. Therefore, interventions should include providing a supportive environment both at school and at home. Understanding 24-hour movement behavior patterns is also needed to design an integrated healthy living strategy. The results of this study are expected to be the basis for policy making in increasing adolescent physical activity in a sustainable manner.